Implementation of Active Learning Method in Unit Operations II Subject - Sholeh Ma'mun (International Journal of Chemistry Education Research, 2018)
ABSTRACT: Active Learning Method which requires students to take an active role in the process of learning in the classroom has been applied in Department of Chemical Engineering, Faculty of Industrial Technology, Islamic University of Indonesia for Unit Operations II subject in the Even Semester of Academic Year 2015/2016. The purpose of implementation of the learning method is to assist students in achieving competencies associated with the Unit Operations II subject and to help in creating a conducive academic atmosphere so as to contribute to improving the quality of teaching and learning in the study environment. The implementation of this learning method synergized with the face-to-face method is quite successful. This is indicated by an increase in the students' final score ofB from the baseline by 44% to 80%. This achievement exceeds the targeted percentage of 60%.Keywords: active learning method, face to face method, process of learning, conducive academic atmosphere, unit operations IIReceived: 6 February 2018, Revised: 15 February 2018, Accepted: 25 February 2018